Do Chronic Pain Patients Wish Spiritual Aspects to Be Integrated in Their Medical Treatment? A Cross-Sectional Study of Multiple Facilities - Hasenfratz, Karin; Moergeli, Hanspeter; Sprott, Haiko; Ljutow, André; Hefti, René; Rittmayer, Isabelle; Peng-Keller, Simon; Rufer, Michael (Frontiers in Psychiatry, 2021)
Objective. Chronic pain is a complex, multidimensional experience. Spirituality is hypothesized to impact pain experience in various ways. Nevertheless, the role that spirituality plays in multimodal pain therapy remains controversial and, to date, quantitative data on whether and for which patients spiritual aspects should be considered in the treatment of chronic pain is lacking. The aim of this study was thus to investigate the proportion and characteristics of patients with chronic pain who wish spiritual aspects to be integrated in their treatment. Methods. Two hundred nine patients with chronic pain were recruited from five inpatient departments and outpatient clinics in the German-speaking part of Switzerland. Patients filled out validated questionnaires, such as the Hospital Anxiety and Depression Scale (HADS), the Resilience Scale (RS-11), the Spiritual and Religious Attitudes in Dealing with Illness (SpREUK), and the 12-item Spiritual Well-Being Scale (FACIT-Sp-12). Results. More than 60% (61.7%) of the patients wanted to address spiritual aspects in their treatment. These patients were significantly younger, had higher levels of education, and suffered from more frequent and more severe pain than patients who did not wish to address spiritual aspects. Furthermore, there were high correlations with existing spiritual resources and higher scores of spirituality. Conclusions. These results confirm that the majority of chronic pain patients wish spiritual aspects to be considered in their treatment. Additionally, the finding that these patients had more spiritual resources underlines the importance of integrating spiritual aspects in a resource-oriented, patient-centered care approach for this condition.